Telenursing Improving Health Literacy Among Pregnant Women - Nurul Fadhilah Gani; Huriati; Nurhidayah; Nur Risma (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2022)
Health literacy among pregnant women refers to ability to access, selecting, understand, and used information during pregnancy. The good health literacy is an important component of maternal health. In Indonesia especially Gowa district of south Sulawesi, health literacy among pregnant women still low. In this regards, it is important to improving health literacy among pregnant women through some strategies. Telenursing is a trending media of education to improve health literacy. This study aimed to determine the effectiveness of telenursing through video and whatsapp groups on increasing health literacy skills in pregnant women. This study was a quantitative study with a non-equivalent design. The population were 77 pregnant women. The study examined 38 pregnant women first and second semester who attend primary health Samata, Gowa Regency. Purposive sampling technique were used in this study. Data were collected by complete the HLS-EUQ16 Questionnaire which consist by 16 questions. Data were analyzed using Wilcoxon rank to analyzed the effectiveness of video and whatssapp pre and post intervension. p value 0.000 and 0.001 which were mean that video and whatsapp as an effective media to improved health literacy among pregnant women in the Samata primary Health care. Mann Whitney U were used to analyzed the differences between video and whatsapp as a telenursing media for improving health literacy. P value were 0.08, that were mean there are no differences between video and whatsapp for improving health literacy among pregnant women. The conclusion were telenursing is an effective media for improving health literacy among pregnant women.Thus, it is recommended to use video and whatsapp as a education media to improve the health literacy.